2023
DOI: 10.1021/acs.est.2c08581
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicity Evaluation of Fire-Extinguishing Water from Large-Scale Battery and Battery Electric Vehicle Fire Tests

Abstract: Electrified transport has multiple benefits but has also raised some concerns, for example, the flammable formulations used in lithium-ion batteries. Fires in traction batteries can be difficult to extinguish because the battery cells are well protected and hard to reach. To control the fire, firefighters must prolong the application of extinguishing media. In this work, extinguishing water from three vehicles and one battery pack fire test were analyzed for inorganic and organic pollutants, including particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…To assess this, the best method would be to test the particle mix directly. Few studies of this kind are available but, Yang et al has recently shown [8] that particles from NMC cell thermal runaway could cause inhibition on bacterial activities in the range of 25-200 mg/l and severe acute toxicity at 100 mg/l in 5h [8] and Quant et al show the acute toxicity of the runoff water [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess this, the best method would be to test the particle mix directly. Few studies of this kind are available but, Yang et al has recently shown [8] that particles from NMC cell thermal runaway could cause inhibition on bacterial activities in the range of 25-200 mg/l and severe acute toxicity at 100 mg/l in 5h [8] and Quant et al show the acute toxicity of the runoff water [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, more globally, published information regarding contamination of fire waters used to tackle li-ion battery fires, regardless of the application, remains quite scarce. Therefore, further investigation is needed to confirm early trends observed [19] and to address those issues on the entire value chain of LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…To assess this, the best method would be to test the particle mix directly. Few studies of this kind are available but, Yang et al has recently shown [8] that particles from the NMC cell thermal runaway could cause inhibition of bacterial activities in the range of 25-200 mg/L and severe acute toxicity at 100 mg/L in 5 h [8] and Quant et al showed the acute toxicity of the runoff water [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, more globally, published information regarding contamination of fire waters used to tackle li-ion battery fires, regardless of the application, remains quite scarce. Therefore, further investigation is needed to confirm the early trends observed [19] and to address those issues in the entire value chain of LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…Here, at any of the life cycle stages, the wrong treatment of chemicals or accidents may lead to severe impacts on the environment and human health. 21,24 However, it is difficult to identify potentials hazards in early technology development stages (or technology readiness levels -TRL) due to two aspects, as follows: (i) there is no common standard for these assessment methods 4 and (ii) there is often no sufficient data available for a robust assessment of new chemicals. Additionally, there may be a high number of potential material combinations that have to be screened but for which data are only available on a lab-scale level.…”
Section: Literature Reviewmentioning
confidence: 99%